2015
DOI: 10.5709/acp-0171-1
|View full text |Cite
|
Sign up to set email alerts
|

Expertise, Working Memory and Articulatory Suppression Effect: Their Relation with Simultaneous Interpreting Performance

Abstract: Simultaneous interpreting is a complex bilingual verbal activity that involves the auditory perception of an oral communication and the production of a coherent discourse. One of the cognitive functions underlying simultaneous interpreting is working memory. The aim of this work was to study the relationship between expertise, working memory capacity and articulatory suppression effect, and the ability to perform simultaneous interpreting. For this purpose, four working memory tasks and one simultaneous interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…These results are not good enough for us to make claims about the presence or absence of an interpreter advantage in WM spans. They could be reflections of the elusive nature of an interpreter advantage in complex verbal spans (generally verbal reading and listening spans) in the literature (e.g., advantage in Köpke and Nespoulous, 2006 ; Zhang, 2008 ; but no such advantage in Liu et al, 2004 ). With more training or with higher L2 proficiency, the relationship between CI performance and L2 listening span at least could be stronger, but more research is certainly needed to verify this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are not good enough for us to make claims about the presence or absence of an interpreter advantage in WM spans. They could be reflections of the elusive nature of an interpreter advantage in complex verbal spans (generally verbal reading and listening spans) in the literature (e.g., advantage in Köpke and Nespoulous, 2006 ; Zhang, 2008 ; but no such advantage in Liu et al, 2004 ). With more training or with higher L2 proficiency, the relationship between CI performance and L2 listening span at least could be stronger, but more research is certainly needed to verify this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…There are similar cases in the literature. For example, Zhang (2008) conducted a longitudinal study with three groups of participants: beginning interpreting trainees, advanced interpreting trainees, and professional interpreters (their age means were 23.4, 23.6, and 32.3, respectively), and comparing each group’s pretest and posttest scores (paired t -test), found that the beginning trainees’ reading span and advanced trainees’ coordinating ability were significantly improved by the 6 months’ experience of interpreting. Macnamara and Conway (2014) tested twice a group of 21 bimodal bilinguals with 2 years in between when participants received SI between American Sign Language (ASL) and English, and found that interpreting training enhanced the WM component processes of coordination and transformation (as tested by backward digit span and letter–number sequencing), but not processes of storage and processing (as tested by reading span and operation span).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, recall efficiency in this population only seems significantly greater when subvocal rehearsal is impeded – i.e., in scenarios that replicate the processing conditions of actual SI. In fact, whereas interpreting performance correlates with WM under articulatory suppression, no such association emerges when subvocal rehearsal is allowed (Injoque-Ricle et al, 2015).…”
Section: Evidence From Interpreting Studentsmentioning
confidence: 99%
“…Simultaneous interpreting (SI) is a highly complex verbal task, requiring listening and comprehension of the source language. It involves the temporary storage and extraction of the meaning ( Christoffels et al, 2004 , 2006 ; Tzou et al, 2012 ; Injoque-Ricle et al, 2015 ; Aparicio et al, 2017 ), reformulation of previous information segments into the target language, and the articulation of even earlier segments ( Gerver, 1976 ; Padilla Benitez et al, 1995 ). Also, cultural nuances and communication rules have to be taken into consideration while retrieving information on how to convey the meaning of the source language ( Christoffels et al, 2004 ; Liang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that interpreters with higher level of expertise outperform non-interpreters in WM capacity (e.g., Padilla Benitez et al, 1995 ; Christoffels et al, 2006 ; Shen and Liang, 2015 ; Dong et al, 2018 ). However, Liu et al (2004) and Injoque-Ricle et al (2015) claimed that no significant difference in WM exists across professional interpreters with different length of experience. As for the second question, a significant difference in SI performance between different WM groups has been reported several times, with higher WM contributing to better SI performance (e.g., Padilla Benitez et al, 1995 ; Tzou et al, 2012 ; Zhang, 2012 ; Injoque-Ricle et al, 2015 ; Macnamara and Conway, 2016 ).…”
Section: Introductionmentioning
confidence: 99%